Identification and genetic determination of an early life risk disposition for depressive disorder: Atypical stress-related behaviour in early childhood - van Eekelen, A.; Olssen, C.; Ellis, J.; Ang, W.; Hutchinson, D.; Zubrick, Stephen; Pennell, C. (Taylor & Francis Ltd., 2011)
Progress in psychiatric genetics has been slow despite evidence of high heritability for most mental disorders. We argue that greater use of early detectable intermediate traits (endophenotypes) with the highest likely aetiological significance to depression, rather than complex clinical phenotypes, would be advantageous. Longitudinal data from the Western Australian Pregnancy Cohort (Raine) Study were used to identify an early life behavioural endophenotype for atypical hypothalamic-pituitary-adrenocortical function in adolescence, a neurobiological indicator of anxiety and depression. A set of descriptors representing rigid and reactive behaviour at age 1 year discriminated those in the top 20% of the free salivary cortisol exposure at age 17 years. Genetic association analysis revealed a male-sensitive effect to variation in three specific single nucleotide polymorphisms within selected genes underpinning the overall stress response. Furthermore, support for a polygenic effect on stress-related behaviour in childhood is presented.